An unusual case of huge hamartoma of breast in a 23 year old female: a case report - Tele, Jyoti Shankar; Patil, Nanda J.; Bhosale, Suresh; Gupta, Sonal Omprakash (International Journal of Research in Medical Sciences, 2018)
Breast hamartoma is an underdiagnosed and poorly recognized rare benign lesion, accounting for approximately 4.8% of all benign breast lumps. There is lack of awareness of the characteristic clinical and histologic features of this entity in clinicians and pathologists. The pathogenesis of the development of breast hamartoma is still not fully understood. A 23-year-old female presented with a huge painless lump in right breast. The lump was present since last nine years. It was previously of the size of a bean, which rapidly increased to the present size during her pregnancy. FNAC revealed features of lipoma. However, on histopathological examination diagnosis of Hamartoma was rendered. A definitive diagnosis of hamartoma is hard to achieve on clinical examination, imaging studies and fine needle aspiration cytology. A correlation of histology, imaging findings with clinical impression is necessary.